Chemical constituent influence on ionizing radiation treatment of a wood–plastic composite. (July 2016) - Palm, Andrew; Smith, Jennifer; Driscoll, Mark; Smith, Leonard; Scott Larsen, L.
Abstract: A dose range of 0–200 kGy was used to irradiate polyethylene-based wood plastic composite (WPC) specimens. An evaluation of mechanical properties in bending resulted in an increase in ultimate strength, but little effect to stiffness. The bending test results were compared to previous testing in order to examine reproducibility. Hardness tests were also conducted, revealing an increase at a dose range of 0–250 kGy. Highlights: Feasibility of electron beam treatment of a wood plastic composite. No significant impact on modulus of elasticity. Increase in ultimate strength and hardness.